Circumstances of falls and fall-related injuries among frail elderly under home care in China - Hong-Ying Pi; Meng-Meng Hu; Jie Zhang; Pei-Pei Peng; Dan Nie (Elsevier, 2015)
This exploratory study investigated the circumstances of falls and fall-related injuries among frail elderly people under home care. A convenience sample of 500 frail elderly (60-99 years old) from the Wanshoulu and Yuyuantan communities in Beijing's Haidian District during February 2013 and March 2014. Fall circumstances and related injuries were characterized by detailed interviews and questionnaires. The article reports the results of a study that the overall fall incidence was 41.5%, and higher for females than males. Falls mainly occurred in individuals who were over 80 years old (50.0%) and indoors (67.9%). The percentage of subjects who experienced a combined injury after the fall was 56.3%, whereas 19.0% fell causes a fracture. Approximately 35% of the subjects were hospitalized, and 27.6% of the subjects recovered more than 30 days. Results indicate that, falls in the frail elderly caused serious damage, and fall-related circumstances should be a great concern in this population.